Computational study of LnGaO3 (Ln=La+Gd) perovskites - Gale, Julian; Senyshyn, A.; Ehrenberg, H.; Vasylechko, L.; Bismayer, U. (IOP Publishing Ltd, 2005)
Atomistic simulation techniques have been used to study the thermal properties of perovskite-type LnGaO3 (Ln = La-Gd). A set of interatomic potentials describing interatomic interactions in these compounds was developed and tested over a wide temperature range through utilizing free energyminimization.The predicted dielectric constants, thermal expansion coefficients, phonon density of states and its projections, heat capacity and entropy, elastic moduli, Gruneisen parameters, surface energies for main crystallographic directionsand Debye temperatures are in good agreement with the limited available experimental data. Perovskite-type LnGaO3 (Ln = La-Gd) compounds have been examined under conditions to which substrate materials are typically subjected. Only a narrow region in the phase diagram of LnGaO3 (Ln = La-Gd) and their solid solutions is recommended for use in substrate applications.